2021
DOI: 10.1016/j.jad.2021.03.064
|View full text |Cite
|
Sign up to set email alerts
|

No psychological vaccination: Vaccine hesitancy is associated with negative psychiatric outcomes among Israelis who received COVID-19 vaccination

Abstract: Background The widespread COVID-19 vaccination program, issued by the Israel Government, provides a unique opportunity to examine psychiatric morbidity and vaccine attitudes among individuals who have already been vaccinated. Accordingly, the current study examined how vaccination hesitancy contributes to clinical levels of depression, anxiety, and peritraumatic stress among individuals who had received COVID-19 vaccinations. Methods We analyzed data obtained from 254 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 8 publications
10
63
1
3
Order By: Relevance
“…In this study, psychological distress was positively associated with COVID-19 vaccine hesitancy, which was in keeping with the results among Israelite vaccinated individuals ( Palgi et al, 2021 ). The possible mechanism may lie in the link of psychological distress with vaccine worries, since we detected a higher proportion of safety concern among distressed parents than non-distressed counterparts (59.0% vs. 55.5%, data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, psychological distress was positively associated with COVID-19 vaccine hesitancy, which was in keeping with the results among Israelite vaccinated individuals ( Palgi et al, 2021 ). The possible mechanism may lie in the link of psychological distress with vaccine worries, since we detected a higher proportion of safety concern among distressed parents than non-distressed counterparts (59.0% vs. 55.5%, data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Issues like reports of sudden adverse events, negative mood before injection, schedule rearrangement, etc. may all lead to the potential reluctance to get vaccinated [48,49], especially among those who are suspicious with normal or low levels of vaccination confidence, which was supported by our results. Participants with willingness but without confidence reported a significant rate of unvaccination, compared to those who trusted in two or more dimensions of vaccination confidence.…”
Section: Discussionsupporting
confidence: 84%
“…A previous study showed that healthcare workers with depression had a lower likelihood of taking a COVID-19 vaccine [ 25 ]. In turn, when they took the vaccine, the vaccine hesitancy showed a negative impact on their mental health [ 74 ]. Fear of COVID-19 and perceived stress were not found to be associated with vaccine hesitancy in our study.…”
Section: Discussionmentioning
confidence: 99%